Developing gender transformative approaches to strengthen women’s land rights in the Gambia: Foundational gender analysis - North, Hanna; Paez Valencia, Ana Maria; Morgan, Miranda (2024)
Innovative approaches are needed to achieve the United Nation’s Agenda 2030, including reducing gender and other social inequalities. Land rights, understood here broadly as bundles of rights to access and make decisions over the use of land, is one area where inequalities are particularly prevalent. In development practice and policies, interventions that aim to support gender equality and land rights have often failed to effectively address the root causes of inequality. Integrating Gender Transformative Approaches (GTAs) into these interventions can improve land rights practices and outcomes.